2017
DOI: 10.3390/nano7060131
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Types, Their Synthesis, Properties and Incorporation in Direct Solar Thermal Collectors: A Review

Abstract: The global demand for energy is increasing and the detrimental consequences of rising greenhouse gas emissions, global warming and environmental degradation present major challenges. Solar energy offers a clean and viable renewable energy source with the potential to alleviate the detrimental consequences normally associated with fossil fuel-based energy generation. However, there are two inherent problems associated with conventional solar thermal energy conversion systems. The first involves low thermal cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(70 citation statements)
references
References 230 publications
0
68
0
2
Order By: Relevance
“…Another onestep approach also exists [112,113], with all being favourable in minimizing the agglomeration of nanoparticles in the basefluid. However, the downside of using the one-step approach is the presence of contaminations that are difficult to dispose of [106]. Figure 7 shows a sample of the one-step approach used to prepare nanofluids by vapour deposition.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another onestep approach also exists [112,113], with all being favourable in minimizing the agglomeration of nanoparticles in the basefluid. However, the downside of using the one-step approach is the presence of contaminations that are difficult to dispose of [106]. Figure 7 shows a sample of the one-step approach used to prepare nanofluids by vapour deposition.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…In order to commercialise such type of advanced fluids, some factors are required to be improved and better understood by researchers. Examples of these factors are listed below [13,26,82,99,106,213]:…”
Section: Challenges Of Nanofluids and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are some reviews on nanofluid based solar collectors. Chamsa-ard et al [15] reviewed the nanofluid types, synthesis, properties and applications in direct solar thermal collectors. They concluded that the stability and , 0 (201 Web of Conferences https://doi.org/10.1051/e3sconf/2019111010 9) 201 E3S 111 10 CLIMA 9 56 56 thermal conductivity are important performance parameters for solar collectors.…”
Section: Solar Collectorsmentioning
confidence: 99%
“…The results of density of samples were given initial reaction effects of sunlight exposed [32] of SiNPs and f-SiNPs with biocompatible molecules on a constant temperature 25 °C. The density (ρ) properties of nanoparticles were determined by used of the densitometer.…”
Section: Density Analysis Of Photo Energy Harvestingmentioning
confidence: 99%